2018
DOI: 10.1016/j.sjbs.2017.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Plumbagin inhibits neuronal apoptosis, intimal hyperplasia and also suppresses TNF-α/NF-κB pathway induced inflammation and matrix metalloproteinase-2/9 expression in rat cerebral ischemia

Abstract: Cerebral ischemic damage and infarction are well documented in stroke, which is presenting a foremost health concern globally with very high mortality and morbidity rates. Mechanisms that are associated with excitotoxicity, inflammation and oxidative stress are found to be critically involved in ischemic damage. Adverse effects of current therapies are imposing the need in development of neuroprotective agents that are very effective. To explore this we experimentally induced ischemic brain injury and investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 38 publications
4
23
0
Order By: Relevance
“…Nevertheless, other researchers reported that NF-κB is also involved in molecular pathway of neuronal apoptosis [9] and malaria infection [18]. In these two papers, the scientific evidences reported that NF-κB was associated with MMP9 protein modulation also [9,18]. Our result demonstrated that not only the modulation of p65 in BV-2 cells (Figure 4) but also the modulation of p65 is concurrently associated with MMP9 expression ( Figure 3).…”
Section: Resultssupporting
confidence: 47%
See 3 more Smart Citations
“…Nevertheless, other researchers reported that NF-κB is also involved in molecular pathway of neuronal apoptosis [9] and malaria infection [18]. In these two papers, the scientific evidences reported that NF-κB was associated with MMP9 protein modulation also [9,18]. Our result demonstrated that not only the modulation of p65 in BV-2 cells (Figure 4) but also the modulation of p65 is concurrently associated with MMP9 expression ( Figure 3).…”
Section: Resultssupporting
confidence: 47%
“…So far, it is known that NF-κB plays a pivot role inside the program of transcription activation in different types of pathologies [5,11,16,38]. Nevertheless, other researchers reported that NF-κB is also involved in molecular pathway of neuronal apoptosis [9] and malaria infection [18]. In these two papers, the scientific evidences reported that NF-κB was associated with MMP9 protein modulation also [9,18].…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…66) TNF-α/NF-κB pathway has been recognized as one of the key pathways in the development of inflammation in many diseases, including MI. 67,68) In addition, an increase TNF-α expression has been reported to induce cardiomyocyte apoptosis, thus exacerbating the myocardial damage. 69) Interestingly, we discovered that TNF-α expression was highly upregulated in H/R model, which was in line with previous research.…”
Section: Discussionmentioning
confidence: 99%